Gamification Ethics - Sami Hyrynsalmi; Kai Kimppa; Jouni Smed (Springer, 2022)
Gamification ethics refers to the study and understanding of right and wrong conducts by or with gamified solutions. As gamification taps into the natural playfulness of human beings, ethical issues are prevalent and must be considered by the developers.
Encyclopedia of Computer Graphics and Games